EVALUATION OF STUDENTS CONCEPTUAL UNDERSTANDING IN THE COURSE MULTIPLE VARIABLE CALCULUS - Ayu Yarmayani (PT. Jurnal Center Indonesia Publisher, 2026)
Calculus of Multiple Variables is a core course in the Mathematics Education study program and plays a crucial role in developing students advanced mathematical thinking skills. Success in this course relies heavily on mastery of the prerequisite material, particularly the concepts of derivatives and integrals of functions of one variable. Therefore, understanding mathematical concepts is a fundamental aspect that determines students’ ability to understand the interrelationships between topics and solve problems systematically and logically. This study aims to describe students' conceptual understanding of multivariable calculus. The approach used is a descriptive approach with a purposive sampling technique, namely selecting research subjects based on certain criteria in the form of the highest and lowest levels of mathematical concept understanding. The results of the study indicate that students conceptual understanding varies across different materials. In the partial derivative material, students were not yet fully able to accurately represent the solution concept, especially in applying the rules for derivatives of exponential functions, so the results obtained did not conform to mathematical principles. These errors are conceptual in nature and indicate a weak grasp of certain basic concepts. However, in the material on derivatives of products of two functions and triple integrals, students demonstrated goog conceptual understanding. They were able to select, use, and apply solution procedures appropriately and systematically. This finding indicates that despite weaknesses in certain concepts, students still possess quite good procedural and conceptual abilities in the context of other problems in polynomial calculus.